Superconductivity above 250 K in Tl1.8Ba2.0Ca2.6Cu3.0O10+dat high pressure - Han, C. Y.; Yin, B.; Tang, D. S.; Lin, W.; Wu, Y. S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The pressure dependence of the superconducting transition temperature Tc(onset) of Tl1.8Ba2.0Ca2.6Cu3.0O10+d (Tl-2223) has been measured under quasi-hydrostatic pressure (QHP) up to 5.0 GPa. The Tc increases with increasing pressure at a relatively high rate and reaches a maximum at 255.4 K and pressure of about 4.3 GPa. This is the highest Tc yet observed for any high-Tc superconductor. The total change in Tc from ambient condition (Tc=129K) to the high pressure applied can be greater than 126 K. The Tc above 200 K was replicated several times in our experiments. The site of the maximum of Tcn and the value of dTc/dP=1.7K/GPa (at P = 0) agree with previous results obtained by D. Tristan Jover et al. [1] and J. G. Lin et al. [2], respectively.